Prospective study of inferior limb amputations. - Henderson, Eduardo; Schimchak, Mario (Cirugía del Uruguay, 1988)
87 amputations of the inferior limb of vascular origin in patients from the "Hospital de Clínicas" between 1981 and 1985 are analized. The incidence related lo the amputation level shows a higher rate in above knee amputations. Hospitalization days and morbility are signi• ficantly elevated in below knee amputations